THE EFFECT SAP APPLICATION SYSTEM QUALITY AND THE QUALITY OF INFORMATION ON INDIVIDUAL PERFORMANCE DIMEDIATE USER SATISFACTION (At PT. PLN (Persero) CENTRAL JAVA AND D.I.YOGYAKARTA DISTRIBUTION MAIN UNITS) - Umi Dwi Rahayu; Umar Chadhiq (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
This research aims to analyze and find empirical evidence about SAP application system quality and the quality of information on individual performance dimediate user satisfaction. The populations of this research were employees at PT PLN (Persero) Main Distribution Unit for Central Java and DIYogyakarta. The samples in this research were 60 respondents. The data are collected by distributing questionnaires. The sampling technique in this research used the Slovin formula and the data were processed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) approach with the help of the WarpPLS 6.0 program and a significance level of 10%. The results showed that (1) system quality had a positive and insignificant effect on user satisfaction with a path coefficient of 0.12 and p-values of 0.17 so that (0.17 > 0.10), (2) the quality of information had a positive and significant effect. on user satisfaction because it produces a path coefficient of 0.45 with p-values